Pemberdayaan Perempuan dalam Pertunjukan Wayang Kulit: Upaya Penyetaraan Gender oleh Dalang Perempuan - Latifa Ramonita; Joe Harrianto Setiawan; Rudi Sukandar; Edhy Aruman (Jurnal Komunikasi Pembangunan, 2023)
In wayang kulit (shadow puppetry), the position of dalang or puppeteer is very crucial. Dalang is the show director, writer, narrator, musician, and not infrequently singer. Public preference and media exposure for women dalangs are, unfortunately, still lacking, thus affecting their future compared to those of men dalangs. Negative assumptions, such as that women dalangs are less exciting and not supposed to be dalangs, also contribute to the problem. This study attempts to highlight how women dalangs empower themselves so they can be considered equal as men dalangs, using the Three-Dimensional Model of Women Empowerment by Huis et al. This study was conducted using qualitative method with critical ethnography design, by interviewing 4 women dalangs and 2 men dalangs in the city of Solo, Central Java, and Jogjakarta. The result of this study shows that women dalangs are still facing difficulties in showmanship, especially in technical skills. They also need more collaboration with wayang communities to develop their career and existence. Furthermore, show varieties and a strong storytelling also become two important factors to differentiate them from men dalangs. These findings provide insight into the situation in Indonesia’s wayang kulit industry, with implications for gender equality and women empowerment.